Negotiating Practice: An analysis of an institutional dialogue about networked learning - Foster, Jonathan; Bowskill, Nicholas; Lally, Vic; McConnell, David (Proceedings of the International Conference on Networked Learning, 2000)
The following paper analyses data which has emerged from a strand of the TLTP3 Computer Based Collaborative Group Work (CBCGW) project focusing on the topic of ‘institutional readiness for networked learning’. The purpose or the strand to date has been to survey and evaluate the readiness of a traditional, research-led university for implementing networked learning, specifically, networked collaborative learning. As such the survey has been concerned with a potential change process. One aspect of a potential change process is a concern with the meaning of such a process for the participants concerned (Fullan, I 99 I; Wenger, I 998). Drawing on the theoretical framework of communities-of-practice and on data from interviews with university staff the paper explores the economies of meaning at the University and the implications for the university’s capacity to learn about networked learning.